Incentives and selection in promotion contests: Is it possible to kill two birds with one stone? - Rudi Stracke; Wolfgang Höchtl; Rudolf Kerschbamer; Uwe Sunde (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2014)
This paper investigates whether a designer can improve both the incentive provision and the selection performance of a promotion contest by making the competition more (or less) dynamic. A comparison of static (one-stage) and dynamic (two-stage) contests reveals that this is not the case. A structural change that improves the performance in one dimension leads to a deterioration in the other dimension. This suggests that modifications of the contest structure are an alternative to strategic handicaps. A key advantage of structural handicaps over participant-specific ones is that the implementation of the former does not require prior identification of worker types.
Keywords: M52; J33; 330; Promotion Contests; Heterogeneity; Incentives; Selection; Handicapping